Fungal pathogens in dermatological lesions of large and small animal species in veterinary clinics and animal shelters in Bogotá D.C. - Peña-Castillo, Zully Mariana (2021)
The aim of this study was to determine the presence of fungal pathogens from dermatological lesions of large and small animal species in veterinary clinics and animal shelters in Bogotá, Colombia. From a total of 30 canines, 15 felines and 2 equines, skin scraping samples (31) and otic (26) and skin (44) swabs were obtained, which were analysed by direct examination, culture and identification at the species level. Microsporum canis and Malassezia spp were mainly identified. According to the animal species, M. canis (21.4%) predominated in felines and Malassezia pachydermatis (32.1%) in canines. According to the type of sample, a higher frequency of M. canis was detected in skin scraping (21.4%) and Malassezia spp in ear swabbing (21.4%).